Practitioner-driven recommendations for the professional evaluation of the strength and conditioning coach - Gleason, B. H.; Bellon, C. R.; Szymanski, D. J. (Strength and Conditioning Journal, 2020)
The purpose of this article is to provide a practical framework for athletic administrators and senior coaches to use in evaluating a strength and conditioning coach (SCC) under their supervision. A formal objective evaluation process may improve training outcomes, prevent common troublesome issues in the field, increase accountability, and optimize organizational dynamics. Recommendations include planned, systematic, and documented observation of work performed, review of performance testing data, and developmental feedback meetings between the SCC and the supervisor. Some modification may be necessary for each sector of the field. However, the general themes may still be followed by supervisors